BERPOLIGAMI: ANTARA HAK SUAMI DAN HAK ISTERI MENURUT UNDANG-UNDANG KELUARGA ISLAM DI MALAYSIA - Abdullah, Raihanah (Jurnal Syariah, 2019)
In the beginning of 1980s, specific and detailed provisions on polygamy were enacted under the Islamic Family Law Enactment. One of the purpose of this provision is to control the practice in order to avoid difficulties and problems (if any) faced my Muslim Women. In some cases, women suffer financially and emotionally when their husband abuse the permission granted by the Qur' an. Therefore, this article discusses the rights of Muslim Women in polygamous marriage as provided under Islamic Family Law Enactment and to what extent the law protects muslim women from any abuses in such marriages.